Genetic Factors in Radiation Resistance of Bacillus subtilis - Zamenhof, Stephen (1965)
Zamenhof, Stephen (University of California, Los Angeles), Hela Bursztyn, T. K. Ramachandra Reddy, and Patrice J. Zamenhof. Genetic factors in radiation resistance of Bacillus subtilis. J. Bacteriol. 90:108–115. 1965.—A study of several wild cross-transformable strains of Bacillus subtilis revealed differences in the resistance of their spores to X rays. Closer study of two such strains revealed differences of the same type when vegetative cells were exposed to X rays or to ultraviolet light (UV). Cell cultures repeatedly exposed to sublethal doses of UV (with cultivation between exposures) became more resistant to UV, presumably by enrichment in a more UV-resistant mutant. A sulfanilamide-resistant mutant of one strain (vegetative cells and spores) was less resistant to ionizing radiation; this sensitivity was transferable by transformation. No difference in radiation-induced mutability could be demonstrated in any of the strains studied. It is concluded that, at least in the cases studied, (i) the differences in radiation resistance of spores of different strains are not just a result of a superimposition of a common spore resistance mechanism(s) but rather are an amplification of genetically determined resistance differences in vegetative cells of these strains; (ii) sulfanilamide-resistance locus (p-aminobenzoic acid overproduction locus) is one of the loci of radiation sensitivity; (iii) no evidence was obtained that the differences in radiation resistance of cells or spores can be ascribed to differences in radiation resistance of their deoxyribonucleic acid.